Limitation of mobile head CT scanner (ceretom) image quality in a neurosurgery center - Abdullah@ Yong, Ariz Chong@Chong Chee (2016)
Introduction: Computed tomography (CT) has become the preferred technique in the diagnostic toolkit for head and brain imaging and superior to Magnetic Resonance Imaging (MRI) for the assessment of head injury. Indications for head imaging includes head injury, acute stroke, subarachnoid haemorrhage etc. A more recent development in CT imaging has been the development of a mobile CT scanner which can be beneficial from clinical and economical point of views. Objective: To compare the image quality of CT brain images produced by portable head CT scanner, CereTom, to standard fixed CT scanner. Methods: This was a single center retrospective study involving CT brain images of112 neurosurgical patients admitted to Hospital Sultanah Aminah Johor Bahrufrom December 2014 until March 2015. Hounsfield unit(HU) of all the selected images from CereTom were measured for: air, water and bone. Three observers (2 neurosurgeons and 1 radiologist) evaluated independently the CT brain images acquired on standard fixed CT scanner within 48 hours apart with the CereTom. Each images were evaluated for visualization of lesions, grey-white matterdifferentiation and streak artifacts at 3 different levels which were centrum semiovale, basal ganglia and middle cerebellar peduncles. Each evaluation was scored either 1 (poor), 2 (average) or 3 (good). The scores were sum up forming an ordinal reading of 3 to 9. Results:Hounsfield unit (HU) for measured air, water and bone from CereTom were within the range of recommendedby ACR. Evaluation of streak artifacts demonstrated scores of 8.54 (IQR 0.24) with fixed CT scanner versus 7.46 (IQR 1.16) for CereTom at centrum semiovale (z -5.67), 8.38 ± 1.12 versus 7.32± 1.63 at the basal ganglia and 8.21 ± 1.30 versus 6.97 ± 2.77 at the middle cerebellar peduncles. Comparison of grey-white matter differentiation showed scores of 8.27 ± 1.04 with fixed CT scanner versus 7.21 ±1.41 for CereTom at centrum semiovale, 8.26 ±1.07 versus 7.00 ±1.47 at the basal ganglia and 8.38± 1.11 versus 6.74 ± 1.55 at the middle cerebellar peduncles. Evaluation for visualization of lesions showed scores of 8.86 (IQR 0.09) with fixed CT scanner compared to 8.21 (IQR 0.34) for CereTom at centrum semiovale (z -4.24), 8.93 (IQR 0) versus 8.18 (IQR 0.57) at the basal ganglia (z -5.32) and 8.79 (IQR 0.11) versus 8.06 (IQR 0.41) at the middle cerebellar peduncles (z -4.93). All the results were significant with p value < 0.01. Conclusions: The results of this study showed there wassignificant difference in terms of image quality between the images produced by fixed standard CT scanner and CereTom with the latter being more inferior. However, Hounsfield unit (HU) of images produced by CereTom do fulfil the recommendation by ACR.